The Impact of Experiental Yoga Pop-Up Events and Community Development on Relationship Marketing: A Case Study of Zenyogaspace, South Jakarta - Ningsih, Adrian; Andhyka, Bintang (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The proliferation of healthy lifestyle–oriented communities has underscored the strategic importance of relationship marketing in sustaining member engagement and long-term participation. Within the context of yoga communities, pop-up class events and community development programs constitute salient experiential mechanisms that foster direct interaction and reinforce social cohesion among members. This study aims to investigate the extent to which pop-up class events and community development influence relationship marketing in a yoga community setting. Scholarly inquiry into relationship marketing within local yoga communities remains limited, particularly studies that simultaneously integrate experiential event-based activities and community development as predictive constructs. Employing a quantitative research design, this study utilized an explanatory survey involving 92 yoga community members. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression following rigorous validity, reliability, and classical assumption testing. The results demonstrate that both pop-up class events and community development exert a positive and statistically significant effect on relationship marketing, both individually and collectively. These findings indicate that the strategic integration of experiential events with community development initiatives is effective in strengthening sustainable, long-term relational ties. Overall, this study highlights the critical role of relational strategies in the governance and sustainability of lifestyle-based communities.